Constitutional Freedom Of Speech: Experience Nos Countries Of Western Europe - V. Gelunenko, Valeriya (2021)
O artigo considers variability of constitutional approaches to consolidate freedom of expression in 23 Western European countries. On a methodological basis the research is formed based on the application of various scientific methods gerais and forms of scientific knowledge (analysis, synthesis, deduction, induction, structural-system, formal-logical approach).